Structure Register of Javanese Preachers in Social Media - Miji Lestari, Prembayun; Mujimin, Mujimin; Nugroho, Yusro Edy; Irawati, Retno Purnama (Jayapangus Press, 2025)
Language variations that correlate with social variations in society are interesting and important studies to do. One of the social variations that shows the dynamics of language is the use of Javanese by religious preachers. This study aims to describe and classify the structure and characteristics of registers used by Javanese preachers in social media. The theory used is the language register theory from Halliday and discourse structure. The source of the data comes from the utterances of Javanese-language preachers on Youtube, especially on the Anza channel. KH. Anwar Zahid. The research was conducted using a descriptive qualitative approach. The process of collecting data through observation and listening methods with note-taking techniques. The research data is in the form of words containing registers that show the structure and characteristics of Javanese preachers on YouTube social media. The results of the study show that there is a structure and register characteristics used by Javanese preachers on social media, especially on the anza channel KH. Anwar Zahid. The structure of the register of Javanese-language preachers on the social media Youtube channel KH. Anwar Zahid can be seen in the opening structure, content or core structure, and closing structure. Each of these structures has a register shape that is not the same. The structure of the registers of Javanese preachers studied show that dominant vocabulary or discourse related to Islamic religion emerges and Javanese culture. In addition, it was found that there were specific greeting words, unique abbreviations, humor or jokes that showed the closeness between the congregation and the preacher, namely KH. Anwar Zahid.